Impacto de estilos de apego, necesidad de aprobación social, y regulación emocional en salud mental: Un modelo paralelo de mediación - Salinas-Quiroz, Fernando (2022)
Emotional Regulation (ER) strategies are created depending on the attachment style, as the probability to experiment positive emotions increases. Need for Social Approval (NSA) works as a motivator that guides behavior and facilitates social adaptation, being associated positively with Mental Health (MH). Relationships between attachment styles, ER, SD and MH were evaluated. In total, 469 participants answered the Revised Adult Attachment Scale, the ER Questionnaire, the NSA Scale and the MH Inventory MHI-38. Significant differences were found in all variables regarding attachment styles. Securely attached individuals had the highest psychological wellbeing and used cognitive re-evaluation as an ER strategy. NSA is conceived as a favorable social adjustment strategy that impacts individual’s MH, influenced by attachment styles in interaction with ER.